COMPARISON OF THE MANIFESTATION OF OTOTOXICITY OF PLATINUM-BASED CHEMOTHERAPEUTIC AGENTS IN EXPERIMENTAL RESEARCH CONDITIONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Chemotherapy is one of the main components of treatment of common types of malignant tumors with early metastasis. Platinum-based chemotherapy drugs are widely used in the treatment of malignancies. Representatives of this group of drugs, such as cisplatin and carboplatin, have side effects such as nephrotoxicity, myelosuppression, neurotoxicity and ototoxicity. Ototoxicity is manifested by unilateral or bilateral hearing loss, which may be accompanied by tinnitus. Damage to the hearing organ depends on the dose and cumulative ability of the drug.